A facebook website application implementing the big-five personality theory online analysis - Manigos, Lora M. (2015)
Abstract: Online personality analysis is already common these days through Facebook applications and other social networking sites. It is of growing interest among users especially those who spend most of their time in using Facebook. Some researchers perform a thorough study to have a reliable outcome and to help those people who want to know their online personality. This study is based on the Big-Five Personality Theory or Five ? Factor Model, which is a common medium used by psychologists and researchers. This uses the five dimensions of personality to describe human personality. The five factors are openness-to-experience, extraversion, agreeableness, conscientiousness and neuroticism. The idea of this study was to come up with an efficient personality finding based on the activities online. Some Facebook features were selected and interpreted to come up with the outcome. However, there are limitations to this study for it is only based on the frequencies or the total number of times the user has been posting, liking contents (e.g. photos, videos, statuses and pages), tagging, adding friends, associating with groups, and uploading photos and videos within the last thirty days of using the social networking site. All information used was from the public profile of the user. Results showed that the personality model of some users were not one hundred percent accurate due to some factors and limitations. Its performance, however, is satisfactory as evaluated by a total of 200 Facebook users with a reliability of 80%. The web application developed was able to meet its objectives and produced an outcome that is fairly satisfying and accurate according to the evaluation given by its users.
Thesis (Bachelor of Science in Computer Science). University of the Philippines Cebu